СОВЕРШЕНСТВОВАНИЯ СИСТЕМ РАЗРАБОТКИ ТРЕТЬЕГО КАЛИЙНОГО ПЛАСТА НА РУДНИКАХ ПО "БЕЛАРУСЬКАЛИЙ" - Зубов В.П.; Смычник А.Д.; Кириенко В.М. (My University, 2006)
Выполнен анализ основных недостатков применяемой на рудниках ПО «Беларуськалий» слоевой системы разработки. Обоснована концепция отработки Третьего калийного пласта в условиях глубоких горизонтов.

The analysis of main lacks applied on the ore mines of PA «Belarusskali» of the extraction by layers a system of development is fulfilled. The concept of improvement of the third potassium embedding in conditions of deep levels is justified.
Keywords: 553.632:622.14